SCIENTIFIC METHODS OF PRE-SCHOOL PEDAGOGICS: THE SYSTEM OF PRESCHOOL ORGANIZATION IN UZBEKISTAN (Scientific Conference on Multidisciplinary Studies, 2025)
The article reveals promising directions for improving the preschool educationsystem in terms of children's age characteristics. The possibility of organizing pre-school education focusing on children's natural emotionality is considered.